Beyond The Game: A Phenomenological Study On the Lived Experiences of Game-Based Learning in Physical Education and Health Classes - Liane Kristal L. Pabustan; Samboy G. Nabor (INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH AND ANALYSIS, 2026)
This study explored the lived experiences of game-based learning approaches in Physical Education and Health classes as basis for developing integrative lesson exemplars for Grade 7 learners. It aimed to describe the learners’ experiences with game-based learning, derive meanings from these experiences, identify the major themes that emerged from the coded responses, and use the findings as basis for a framework and sample lesson exemplars. The study employed a qualitative research design using semi-structured interviews with eight Grade 7 participants who had been exposed to game-based and game-based activities in PEH classes. Interview responses were transcribed, coded, and analyzed through thematic analysis. Findings showed that participants generally found game-based learning enjoyable, engaging, and meaningful. They reported that games increased their motivation, sustained participation, and reduced boredom during PEH lessons. The learners also perceived that gameplay helped them understand concepts and skills more clearly through active participation, practice, and direct application. In addition, the findings emphasized the importance of teamwork, peer encouragement, teacher support, clear instructions, and manageable challenges in making game-based learning effective. The thematic analysis generated four major themes: cognitive and skill development through gameplay, affective and motivational engagement in game-based PEH, social participation and enabling conditions, and transfer of values and healthy behaviors beyond class. Based on these findings, the CAST Gamification Integration Framework was developed to guide the design of integrative lesson exemplars in PEH. The study concludes that game-based learning is a meaningful and effective pedagogical approach that may enhance learning, participation, and values formation among Grade 7 learners in Physical Education and Health.